2010
DOI: 10.1366/000370210790918382
|View full text |Cite
|
Sign up to set email alerts
|

Attenuated Total Reflection Fourier Transform Infrared Spectroscopic Investigation of the Postmortem Metabolic Process in Rat and Human Kidney Cortex

Abstract: Attenuated total reflection (ATR) Fourier transform infrared (FT-IR) spectroscopy has been applied to study the short and long term postmortem metabolic processes in rat and human kidney cortexes. The goals of this project were as follows: (1) to investigate the changes of ATR spectra in different rat and human tissues after death, (2) to explore the best mathematical model with different band absorption ratio changes to determine the postmortem interval (PMI), and (3) to establish a preliminary human postmort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 41 publications
0
8
1
Order By: Relevance
“…In Fig. 1, we can see that the amide II band is greater than the amide I band at the later time points, while this result was different with the former reports (15,35–38). In the former reports, the amide II band is lower than the amide I band obviously at the later time points.…”
Section: Resultscontrasting
confidence: 76%
“…In Fig. 1, we can see that the amide II band is greater than the amide I band at the later time points, while this result was different with the former reports (15,35–38). In the former reports, the amide II band is lower than the amide I band obviously at the later time points.…”
Section: Resultscontrasting
confidence: 76%
“…According to previous researches [ 22 , 61 63 ], the process of decomposition may also degrade the components in blood, including metabolites, proteins, saccharides, and nucleic acids. Previous studies also proved that the decomposition process had a significant impact on the FTIR spectra of postmortem substantial organs [ 24 , 25 , 27 ]. In this case, the band at 1126 cm –1 was associated with lactate and selected as an informative region by GA-PLS.…”
Section: Resultsmentioning
confidence: 95%
“…The chemical analysis of the plasma using UV–Vis and ATR–FTIR measurements may be a quick and easy way to provide insights into the postmortem biochemical changes. Previous studies primarily focused on some substantial organs from humans and animals, and the results showed that their FTIR spectra changes were highly correlated with PMI [ 24 27 ]. The aim of the present study was to obtain a complete overview of postmortem changes in blood using UV–Vis and ATR–FTIR spectroscopies and build more accurate and reliable mathematical models to determine PMI.…”
Section: Introductionmentioning
confidence: 99%
“…Our work is focused on the characterization of postmortem changes in biological tissues with the ATR-FTIR technique in order to determine the time after death. In our previous studies, it has been demonstrated that various absorption intensities or area ratios in an infrared spectrum are strongly correlated with PMI in human and animal tissues including brain, kidney cortex, cardiac muscle and lung [19][20][21][22][23] . However, these studies did not make full use of ATR-FTIR for PMI delimitation because only a few parameters were taken into consideration.…”
Section: Attenuated Total Reflectance-fourier Transform Infrared (Atrmentioning
confidence: 99%